2010
DOI: 10.1177/0961203310392428
|View full text |Cite
|
Sign up to set email alerts
|

Chronic autoimmune urticaria as the first manifestation of juvenile systemic lupus erythematosus

Abstract: Chronic urticaria (daily or almost daily symptoms lasting for more than six weeks) is characterized by wheals and erythema, with or without itching. A few case reports have shown chronic autoimmune urticaria at the beginning of systemic lupus erythematosus (SLE), particularly in adults. However, the prevalence of this manifestation in a lupus paediatric population was not studied. During 27 consecutive years, 5419 patients were followed up at our University Hospital and 271 (5%) had juvenile SLE (American Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 11 publications
1
29
0
1
Order By: Relevance
“…We describe a low frequency of CSU in a large population of cSLE patients. Of note, the majority of cSLE patients presented this skin manifestation before or at disease onset, as was also observed previously in case reports of adult and cSLE patients [6,8] .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We describe a low frequency of CSU in a large population of cSLE patients. Of note, the majority of cSLE patients presented this skin manifestation before or at disease onset, as was also observed previously in case reports of adult and cSLE patients [6,8] .…”
Section: Discussionsupporting
confidence: 63%
“…Few case reports have evaluated urticaria either in adult cSLE patients [6][7][8] . However, the prevalence of this manifestation in the pediatric lupus population and the possible associated factors have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis and appropriate treatment involving clinicians across many different specialties are crucial for preventing further manifestations and achieving beneficial long‐term outcomes for patients . Urticaria may present as the initial symptom in these patients before the more classical form of SLE is confirmed . CU‐like lesions may occur in lupus tumidus, urticarial plaque of LE, which is an uncommon LE‐specific but distinct subtype of chronic cutaneous LE…”
Section: Introductionmentioning
confidence: 99%
“…They often suffer additionally from other autoimmune diseases (vitiligo, insulin-dependent diabetes, rheumatoid arthritis, autoimmune hepatitis or autoimmune Hashimoto thyroiditis) [30]. Spadoni et al have reported on cases of urticaria, as the first manifestation of juvenile systemic lupus erythematosus [31]. In terms of treatment, it seems that patients diagnosed with AU need higher doses of antihistamines and/or general modification of therapy, including alternative therapeutic modalities [32,33].…”
Section: Clinical Manifestations Of Autoimmune Urticariamentioning
confidence: 99%